“DESIGN AND CHARCTERIZATION OF MICROSPONGES OF POSACONAZOLE FOR TOPICAL DELIVERY” - HAMZAH, MOHAMMED LAYTH; MAHAL, RAFFAH KHAMIS; SAMEIN, LAITH HAMZA (International Journal of Psychosocial Rehabilitation, 2020)
Carrier technology offers an intelligent approach for drug delivery by coupling the drug to a carrier particle such as microspheres, nanoparticles, etc. to control the delivery rate of active agents to a predetermined site in human body. The study aimed towards formulation development and evaluation of polymeric micro sponges consisting of noncollapsible structures with porous surface through which active ingredients are released in a controlled mannerPreparation of Posaconazole microsponges is done by quasi emulsion solvent diffusion method followed by preparation of microsponge Posaconazole gel. Charactization of Posaconazole microsponges is done by various physical parameters e.g. Particle size (Microscopy), Morphology and Surface topography, Characterization of pore structure, Loading efficiency and production yield, Drug content, Compatibility studies, Resiliency as well as by In vitro drug release studies e.g. drug release study, release kinetics, In vitro anti-microbial study etc. This system has been utilized for the improvement of performance of topically applied drug. MDS technology is now being presently used in cosmetics, over-the-counter(OTC) skin care, sunscreens and prescription products.